2022
DOI: 10.1007/s12274-022-4849-6
|View full text |Cite
|
Sign up to set email alerts
|

The Yin and Yang of the protein corona on the delivery journey of nanoparticles

Abstract: Nanoparticles-based drug delivery systems have attracted significant attention in biomedical fields because they can deliver loaded cargoes to the target site in a controlled manner. However, tremendous challenges must still be overcome to reach the expected targeting and therapeutic efficacy in vivo . These challenges mainly arise because the interaction between nanoparticles and biological systems is complex and dynamic and is influenced by the physicochemical properties of the nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 147 publications
0
21
0
Order By: Relevance
“…Nanoparticle-based drug delivery systems (NDDSs), as a powerful platform for the controlled delivery of cargoes to the target site, have attracted considerable attention in biomedical fields. , For the delivery process, NDDSs should be able to (i) accumulate at the target site with prolonged circulation time after administration, (ii) attach to the cell membrane and enter the cell, and (iii) then undergo controlled release of the loaded cargoes under different stimuli-responsive mechanisms at the subcellular organelle. Due to the high resolution and sensitivity, noninvasive fluorescent imaging is widely used as a first-line method for visualizing bio-nano interactions and dynamic transportation behavior. Using a typical AIEgen TPE, the dynamic delivery and release process of two representative cargoes, small molecule drug doxorubicin (DOX) and nucleic acid, was spatiotemporally visualized. DOX was bound to the surface of the TPE NPs via electrostatic interactions, providing self-indicating TPE/DOX (TD) NPs.…”
Section: Light Up Life: See the Unseenmentioning
confidence: 99%
“…Nanoparticle-based drug delivery systems (NDDSs), as a powerful platform for the controlled delivery of cargoes to the target site, have attracted considerable attention in biomedical fields. , For the delivery process, NDDSs should be able to (i) accumulate at the target site with prolonged circulation time after administration, (ii) attach to the cell membrane and enter the cell, and (iii) then undergo controlled release of the loaded cargoes under different stimuli-responsive mechanisms at the subcellular organelle. Due to the high resolution and sensitivity, noninvasive fluorescent imaging is widely used as a first-line method for visualizing bio-nano interactions and dynamic transportation behavior. Using a typical AIEgen TPE, the dynamic delivery and release process of two representative cargoes, small molecule drug doxorubicin (DOX) and nucleic acid, was spatiotemporally visualized. DOX was bound to the surface of the TPE NPs via electrostatic interactions, providing self-indicating TPE/DOX (TD) NPs.…”
Section: Light Up Life: See the Unseenmentioning
confidence: 99%
“…Although several studies have confirmed the feasibility and effectiveness of these approaches, some challenges remain. These include (1) the elimination of the nanomedicines by the immune system during systemic circulation; (2) the interaction between the targeting ligand and serum proteins, which results in the formation of a protein corona complex and a loss of targeting capability [69] ; and (3) the non-specific expression of several target receptors and transport proteins, which results in drug accumulation within non-target tissues. Fortunately, these challenges are not insurmountable.…”
Section: Nanomedicines For Targeted Drug Deliverymentioning
confidence: 99%
“…From the TEM at different time points, it can also be seen that the edges of nanoparticles are gradually blurred and flocculent substances increased, which was due to the adsorption of various proteins from the serum by the nanoparticles to form an obvious protein corona layer. [37,38] However, the structure of nanoparticles is intact (Figure 1K). The stability experiments of CuP@PPy-ZOL NPs reveal that they can be further applied to biomedical applications in biological systems.…”
Section: Preparation and Characterization Of Cup@ppy-zol Npsmentioning
confidence: 99%